ADAMTS4 and its proteolytic fragments differentially affect melanoma growth and angiogenesis in mice. Issue 2 (12th February 2013) - Rao, Nithya; Ke, Zhiyuan; Liu, Hongrui; Ho, Chao‐Jin; Kumar, Saran; Xiang, Wei; Zhu, Yizhun; Ge, Ruowen
<x xml:space="preserve">Abstract</x> The metalloproteinase ADAMTS4 (ADAMTS, a disintegrin‐like and metalloproteinase with thrombospondin motif)/aggrecanase‐1 is highly expressed in cartilage and has been implicated in human arthritis. Although abundantly expressed in many types of cancer, its role in cancer remains unknown. In this work, we demonstrate for the first time that full‐length ADAMTS4 and its catalytically more active N‐terminal 53 kDa autocatalytic fragment both promote B16 melanoma growth and angiogenesis in mice. In contrast, overexpression of its catalytically inactive E362A mutant or truncated fragments containing only the C‐terminal ancillary domains suppresses melanoma growth and angiogenesis under similar conditions. Structure–function mapping revealed that the single thrombospondin‐type 1 repeat domain is essential and sufficient for the antitumorigenic activity displayed by the catalytically inactive ADAMTS4 isoforms. Suppression of tumor growth and angiogenesis in mice is accompanied by a significant increase in tumor cell apoptosis, whereas tumor cell proliferation is not affected. Importantly, we identified and demonstrated the presence of novel proteolytic fragments of ADAMTS4 containing essentially only the C‐terminal ancillary domains in cultured cells, and also in human cancer tissues, coexisting with full‐length and catalytically active N‐terminal fragments. The contrasting functions toward tumor growth in mice by the wild‐type proteinase and its catalytically inactive mutant correlate with their contrasting influences on angiogenesis signaling pathway molecules in B16 melanoma in mice. Our results suggest a complex role for ADAMTS4 in cancer with the functional balance of protumorigenic and antitumorigenic isoforms likely to act as an important parameter in determining the net influence of this metalloproteinase on tumor growth in vivo.